Cell–cell signaling in blood vessel development and function - Christer Betsholtz (EMBO Molecular Medicine)
Abstract The blood vasculature is an organ pervading all other organs (almost). During vascular development, cell–cell signaling by extracellular ligands and cell surface receptors ensure that new vessels sprout into non‐vascularized regions and simultaneously acquire organ‐specific specializations and adaptations that match the local physiological needs. The vessels thereby specialize in their permeability, molecular transport between blood and tissue, and ability to regulate blood flow on demand. Over the past decades, we have learnt about the generic cell–cell signaling mechanisms governing angiogenic sprouting, mural cell recruitment, and vascular remodeling, and we have obtained the first insights into signals that induce and maintain vascular organotypicity. However, intra‐organ vascular diversity and arterio‐venous hierarchies complicate the molecular characterization of the vasculature's cellular building blocks. Single‐cell RNA sequencing provides a way forward, as it allows elucidation at a genome‐wide and quantitative level of the transcriptional diversity occurring within the same cell types at different anatomical positions and levels of arterio‐venous hierarchy in the organs. In this Louis‐Jeantet Prize Winner: Commentary, I give a brief overview of vascular development and how recent advances in the field pave the way for more systematic efforts to explore vascular functions in health and disease.